2016
DOI: 10.1111/1365-2664.12778
|View full text |Cite
|
Sign up to set email alerts
|

The use of extrafloral nectar in pest management: overcoming context dependence

Abstract: 1. Extrafloral nectar (EFN) provides plants with indirect defence against herbivores by attracting predatory insects, predominantly ants. Decades of research have supported the role of EFN as an effective plant defence, dating back to Thomas Belt's description of ants on acacia in 1874. 2. Despite this extensive body of literature, knowledge of the ecological role of EFN has rarely been applied in the field of pest management. We review the existing literature on the use of EFN in agriculture and consider the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
22
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 36 publications
(25 citation statements)
references
References 143 publications
0
22
1
Order By: Relevance
“…Alfalfa was not flowering in this experiment. Eventually, benefits from alfalfa for natural enemies in this study would thus have been from alternative prey and any extrafloral nectaries [46,52]. In another study in China, enhanced populations of the anthocorid Orius sauteri (Poppius) in the cover-cropped area (alfalfa and Lagopsis supina (Steph.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Alfalfa was not flowering in this experiment. Eventually, benefits from alfalfa for natural enemies in this study would thus have been from alternative prey and any extrafloral nectaries [46,52]. In another study in China, enhanced populations of the anthocorid Orius sauteri (Poppius) in the cover-cropped area (alfalfa and Lagopsis supina (Steph.…”
Section: Resultsmentioning
confidence: 99%
“…Moreover, vetches (e.g., Vicia sepium L. and Vicia sativa L.,) offer carbohydrates in plant sap from special structures, so-called extrafloral nectaries (EFN) [45] in addition to floral nectar (Figure 2a). These EFN glands are assumed to deliver resources to attract predators in order to create some kind of indirect defence against pests [46] and they can be easily exploited due to their exposed nature. For instance, parasitoid Hymenoptera are known to visit EFN of faba bean [47].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Finally, ant activity in agroecosystems can be easily manipulated, for example, by transferring colonies or offering additional food sources and nest sites (e.g., [47,48]). In addition, the manipulation of ant foraging pathways may redirect foragers towards target pests, and can be conducted using plants with EFNs [49].…”
Section: Introductionmentioning
confidence: 99%
“…Although being reasonable (Agrawal and Rutter, 1998 ), surprisingly little evidence has been reported to support this assumption. In fact, the defensive effects of EFN secretion are highly context-dependent (Heil, 2015 ; Jones et al, 2017 ) and EFN secretion can even be counterproductive if ants start to exclude other, more efficient defenders Koptur et al, 2015 ). Inducing EFN secretion with exogenous JA increased the number of defending ants and decreased the number of herbivores showing up on Macaranga tanarius plants (Heil et al, 2001 ), and similar patterns were found on P. lunatus tendrils that were exposed to VOCs or treated with JA to enhance EFN secretion (Kost and Heil, 2008 ).…”
Section: Discussionmentioning
confidence: 99%